1997
DOI: 10.1006/dbio.1997.8728
|View full text |Cite
|
Sign up to set email alerts
|

The POU Geneceh-18Promotes Gonadal Sheath Cell Differentiation and Function Required for Meiotic Maturation and Ovulation inCaenorhabditis elegans

Abstract: In Caenorhabditis elegans, specialized contractile myoepithelial cells of the somatic gonad, the gonadal sheath cells, are closely apposed to oocytes and are required for normal meiotic maturation and ovulation. Previously we found that mutations in the ceh-18 gene, which encodes a POU-class homeoprotein expressed in sheath cells, result in oocyte defects. To determine the basis for these oocyte defects, we have used time-lapse video Nomarski microscopy to observe meiotic maturation, ovulation, and early embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 47 publications
9
88
0
Order By: Relevance
“…Previous studies by others have shown that the myoepithelial sheath cells express MYO-3 (myoA; Fig. 4A-C) and UNC-54 (myoB) myosin heavy chains (Ardizzi and Epstein, 1987) that are also expressed in the striated body wall muscle and that UNC-54 localizes to the outer regions, whereas MYO-3 is limited to the central part of the thick filaments (Rose et al, 1997) as observed in the thick filaments in the striated body wall muscle (Miller et al, 1983). UNC-15 paramyosin was also expressed in the myoepithelial sheath (Ardizzi and Epstein, 1987;Fig.…”
Section: Thick Filamentsmentioning
confidence: 80%
See 3 more Smart Citations
“…Previous studies by others have shown that the myoepithelial sheath cells express MYO-3 (myoA; Fig. 4A-C) and UNC-54 (myoB) myosin heavy chains (Ardizzi and Epstein, 1987) that are also expressed in the striated body wall muscle and that UNC-54 localizes to the outer regions, whereas MYO-3 is limited to the central part of the thick filaments (Rose et al, 1997) as observed in the thick filaments in the striated body wall muscle (Miller et al, 1983). UNC-15 paramyosin was also expressed in the myoepithelial sheath (Ardizzi and Epstein, 1987;Fig.…”
Section: Thick Filamentsmentioning
confidence: 80%
“…Previous studies have shown that unc-54 myosin heavy chain (Rose et al, 1997), lev-11 tropomyosin (Ono and Ono, 2004), pat-10 troponin C (Ono and Ono, 2004), and mup-2 troponin T (Myers et al, 1996) are required for ovulation. Here, we found that the Emo phenotype (22-51%; n ϭ 100) was induced by RNAi treatments in wild-type background for myo-3 myosin heavy chain, unc-15 paramyosin, pat-3 ␤-integrin, deb-1 vinculin, or unc-52 perlecan (Fig.…”
Section: Roles Of the Myofibrillar Components In Ovulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult worms were stained as described (Finney and Ruvkun, 1990). Worm embryos (obtained by cutting gravid adults; Epstein et al, 1993) and dissected gonads (prepared as in Rose et al, 1997) were attached on poly-lysine-coated slides by freeze-cracking, fixed with methanol at Ϫ20°C for 5 min, and stained with antibodies. Rabbit polyclonal anti-tetraThymosin␤ antibody raised against full-length recombinant protein at the Centre d'Economie rurale, Laboratoire d'Hormonologie (Marloie, Belgium) was enriched by affinity purification over tetraThymosin␤ coupled to CNBr-Sepharose 4B (Pharmacia, Piscataway, NJ).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%